Specific of organization of in-plant training process of enterprise workers - Olga N. Borisova; Natalia A. Sizintseva (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article covers the issue of the features of organization of process of in-plant training of workers of enterprise. In-plant training is examined as system and purposeful perfection of professional knowledge and skills on the basis of innovative technologies and enriching of professional advanced experience. In-plant training of workers of enterprise is grounded on the basis of normativelylegal documents regulating this process. In the article dependence of forms of realization of lessons is presented within the framework of in-plant training of workers from the organizers of the professional program, target audience, level of organization of process of training of personnels, degree of connection with practical and professional activity. A variety, variantness and connection, is examined with practical activity of modern active methods of educating of increase to qualification.